The voice performances in the space of Brazilian contemporary poetry - Busato, Susanna [UNESP] (Univ Brasilia, Dept Teoria Literaria & Literaturas, 2016)
This article aims to point out the concepts of performance and voice in Ademir Assuncao's award winning book 2013 A Voz do Ventriloquo - as elements that emerge from the relations between the subject of discourse and the subjects of culture.
Keywords: Ademir Assuncao; voice; performance; Brazilian contemporary poetry